PENGENALAN SAMPAH PLASTIK DAN PENGELOLAANYA BERBASIS ECOBRIKS BAGI SISWA-SISWI SMA NEGERI 5 AMBON - saleky, valentine domaris (Pattimura University, 2024)
Waste is a serious problem that requires special attention. Nowadays, waste has become a problem that is quite difficult to handle in schools. This happens because of the habits of students as consumers who always produce waste, especially plastic, every time they use a product. SMA Negeri 5 Ambon is one of the school's environmental locations which is directly facing the main road and also the waters of Ambon Bay, where there are also coastal ecosystems such as mangroves and seagrass. Until now, there are still some school residents who do not fully understand the aspects of cleanliness. For this reason, efforts are needed to provide education in the form of counseling, outreach and/or training related to pollution. PkM activities are carried out with the aim of increasing the awareness of students in the school environment regarding the impact of waste pollution through assistance provided by FPIK-Unpatti Marine Science lecturers by introducing the concept of Ecobricks as a practical solution to answer this problem.